Surveillance of osteoarticular infections caused by Staphylococcus aureus in a paediatric hospital in Mexico City - Aguilar-Gómez, Nancy Evelyn; Merida-Vieyra, Jocelin; Isunza-Alonso, Oscar Daniel; Morales-Pirela, María Gabriela; Colín-Martínez, Oscar; Juárez-Benítez, Enrique Josué; García de la Puente, Silvestre; Aquino-Andrade, Alejandra (Frontiers in Cellular and Infection Microbiology, 2022)
Staphylococcus aureus is the main aetiologic agent of osteoarticular infections (OAIs) in paediatric patients. The aim of this prospective unicenter study was to describe the phenotypic and genotypic characteristics of S. aureus isolates obtained from OAIs in paediatric patients admitted to tertiary care hospital. Through a surveillance program called OsteoCode, a multidisciplinary team was created and we identified 27 patients with OAIs caused by S. aureus from 2019 to 2021. The susceptibility profile, virulence factors, biofilm formation, pulsed-field gel electrophoresis (PFGE), clonal complex (CC) and sequence type (ST) were determined. In addition, the clinical characteristics and evolution of the patients presented six months after the diagnosis of OAIs were described. Ninety-two percent of the isolates were methicillin-sensitive S. aureus (MSSA). In methicillin-resistant S. aureus (MRSA), SCCmec-II and SCCmec-V were detected. The pvl gene was only observed in MSSA (18.5%) and was associated with highest fever (p=0.015), multiple localization (p=0.017), and soft tissue sites of infection beyond the bone (pyomyositis, pulmonary abscess) (p=0.017). Biofilm formation was detected in 55.6% of isolates. The most common CC were CC5 and CC30 which represent the most common linages for bone and joint infections worldwide. The isolates were distributed in different STs, and ST672 was predominant. MRSA were associated with a longer duration of intravenous treatment and a prolonged hospital stay (p=0.023). Recurrent infection occurred in five children and orthopaedic complications in 33.3% of patients. This is the first study that reflects the epidemiology of S. aureus in OAIs in paediatric patients in Mexico; a clear predominance of MSSA distributed in different STs was observed. Our findings highlight that a multidisciplinary team is required for the diagnosis and treatment of OAIs.